Laparoscopic total extraperioneal mesh hernioplasty is a novel approach for inguinal hernia: our experience over 7 years - Kalwaniya, Dheer Singh; Mahadevan, Ranjith; Arya, Satya V.; Bajwa, Jaspreet Singh; Gowda, Gowtham K.; Narayan, Akshay; M., Vignesh (International Surgery Journal, 2019)
Background: Inguinal hernia surgery is the most common performed surgery all over the world. Among them laparoscopic totally extra-peritoneal (TEP) mesh repair fulfils all the requirements with better clinical outcomes than other procedures. Methods: Data was collected from the inpatient and out-patient records of 60 patients who underwent laparoscopic TEP for unilateral or bilateral inguinal hernia in a single unit in the Department of General Surgery during May 2012-June 2019 including the two years of follow-up. 3D mesh was used for application and was fixed with tackers. Then patients were followed up in outpatient department after 1 week, 2 week, and 3 months, 6 months and yearly up to two years. In every visit post-operative pain (assessed by visual analogue scale), local wound complication (hematoma, seroma, wound infection) and recurrence were noted. The data was collected and evaluated and the results shown. Results: All patients were men, with average age of 36.5 years (range 32-58). On categorization 53 (88.3%) of them had unilateral inguinal hernia and 7 (11.6%) of them had bilateral inguinal hernia. Intra operatively 12 (20%) of them had direct inguinal hernia and 48 (80%) of them had indirect inguinal hernia. Haematoma was seen in 1 patients, surgical emphysema in 3, seroma in 5 and recurrence in 2 patients. Conclusions: Laparoscopic TEP mesh repair was effective and safe tool for hernia repair, in terms of lesser postoperative painless number of hospital days, early recovery and lesser wound complications. However recurrence rates are comparable with other methods of hernia repair.